Factors Associated with Decision to Use a Long-Term Intra Uterine Device: A Path Analysis Evidence - Deviasti, Rindra; Pamungkasari, Eti Poncorini; Murti, Bhisma (Journal of Maternal and Child Health, 2018)
Background: Intra uterine device (IUD) is a highly effective contraceptive method with a 98-99 percent success rate over five years of IUD use. However, its share of modern method mix is pitifully small, at less than 5%, in 63 countries and only 5%